ISLAMIC COUNSELING IN A PHILOSOPHY PERSPECTIVE - Siregar, Alfin (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract: this paper aims to describe Islamic counseling from a philosophical perspective. However, Islamic counseling cannot be separated from the philosophical foundation as a foundation in analyzing the ontology, epistemology and axiology of Islamic counseling. This paper uses a library research approach, where data is obtained and collected from literature studies. Analysis of the data in this paper requires the author's important role in interpreting the data. In the end, the material object of Islamic Counseling philosophy is the same as the object of philosophy in general, namely everything that exists. Islamic counseling study methods can be done by; Normative, Historical, Linguistic, Contextual, Traditional, Critical, Hermeneutic Approaches.